Investigation of surface roughness in micro-electro discharge machining of nonconductive ZrO2 for MEMS application - Sabur, Abdus; A., Moudood; Ali, Mohammad Yeakub; Maleque, Md. Abdul (IOP Publishing, 2013)
Micro-electro discharge machining technique, a noncontact machining process, is applied for drilling blind hole on nonconductive ZrO2 ceramic for MEMS application. A conductive layer of adhesive copper is applied on the workpiece surface to initiate the sparks. Kerosene is used as dielectric for creation of continuous conductive pyrolytic carbon layer on the machined surface. Experiments are conducted by varying the voltage (V), capacitance (C) and rotational speed (N). Correlating these variables a mathematical model for surface roughness (SR) is developed using Taguchi method. The results showed that the V and C are the significant parameters of SR in micro-EDM for nonconductive ZrO2 ceramic. The model also showed that SR increases with the increase of V and C.